my words chunk 2 consonant blends - short vowels - Ibrahim, Yasmine ([Cairo] the author, 2024)
this book ia an educational book that introduces children to the concept of blending consonant sounds with short vowel sounds, this book helps young learners develop their phonics skills and imorove their ability to read and pronounce words with consonnant blends and short vowels
Linguistic notions
Keywords: Language and Languages